Classification characteristics of a chronic low back pain population using a combined McKenzie and patho-anatomical assessment. (December 2016) - Flavell, Carol Ann; Gordon, Susan; Marshman, Laurence
Abstract: Background: Physiotherapists use musculo-skeletal classification systems for patient assessment. Since its early development, the McKenzie lumbar spine assessment (MK) has been incorporated into examination algorithms and combined with a series of patho-anatomical diagnostic tests. No previous studies have used a MK and a combined examination (MK-C) to provide a detailed profile of patients, report and compare the classification characteristics of a chronic low back pain (CLBP) population. Objective: To report the classification characteristics of a CLBP population using MK and MK-C examinations, and conduct inter-classification comparison of the MK-C for demographics, the Oswestry Disability Index (ODI), Roland Morris Disability Index (RM), Modified Somatic Perceptions Questionnaire (MSPQ), symptom duration and intensity. Method: A prospective cross-sectional study conducted in a spinal clinic by a MK trained physiotherapist. Results: Results were obtained in 150 patients. Using MK, 31% ( n = 47) of participants were classified as inconclusive. Following MK-C only 6% of participants remained inconclusive ( n = 9). The most frequent MK-C classification was facet joint syndrome (FJS) (49%). Participants with FJS were significantly older than those classified as discogenic ( p < 0.001; CI 3.96 ̶ 19.74), or mixed ( p < 0.001; CI 5.98 ̶ 36.41). Participants classified as discogenic had significantly higher RM ( p = 0.022) and MSPQ ( p = 0.005) scores than FJS. Conclusion: Results indicated that 94% of CLBP patients could be classified using a MK-C. The most common presentation in CLBP was facet joint syndrome. Age, RM and MSPQ appeared to be distinguishing characteristics of this population. Future studies should be conducted to establish the validity and reliability of the MK-C. Highlights: The MK-C classified 94% of chronic low back pain patients at first attendance. The most common chronic low back pain presentation was facet joint syndrome. Least common classifications were SIJS, postural syndrome, and CI. Increased age was a distinguishing CLBP characteristic for facet joint syndrome. Discogenic pain was distinguished by greater disability and pain somatisation.